2003
DOI: 10.1128/jvi.77.10.5975-5984.2003
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Latency-Associated Nuclear Antigen Induces Expression of the Helix-Loop-Helix Protein Id-1 in Human Endothelial Cells

Abstract: Kaposi's sarcoma (KS)-associated herpesvirus (KSHV) (also known as human herpesvirus 8) is a gamma-2 herpesvirus believed to be the etiologic agent responsible for KS. The pathogenesis of this potentially lifethreatening neoplasm is complex and unclear, and it is currently unknown how KSHV causes KS. Id (named for inhibitor of DNA binding or inhibitor of differentiation) proteins were identified in 1990 and found to be naturally occurring dominant-negative inhibitors of basic helix-loop-helix transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…Efficient KSHV infection was confirmed by high levels of expression of LANA mRNA in infected HDMECs. We found that 3-7% of infected HDMECs were ORF59-positive and 1.5-3% were K8.1 positive, in agreement with previous results [12][13][14] . This indicates that <10% of the cells were undergoing lytic reactivation.…”
supporting
confidence: 82%
“…Efficient KSHV infection was confirmed by high levels of expression of LANA mRNA in infected HDMECs. We found that 3-7% of infected HDMECs were ORF59-positive and 1.5-3% were K8.1 positive, in agreement with previous results [12][13][14] . This indicates that <10% of the cells were undergoing lytic reactivation.…”
supporting
confidence: 82%
“…Whole-cell extracts were prepared by lysing cells in CHAPS buffer containing a mixture of protease inhibitors (MiniComplete, Roche Molecular Biochemicals), incubating the cells for 20 min on ice and centrifuging to remove insoluble cellular debris (Tang et al, 2003). Protein concentration was determined using a Bradford Assay (Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…While many established cells in culture can be latently infected by KSHV, most such cells display no phenotype (2). However, recent studies from several groups show that primary vascular endothelial cells from dermal microvasculature (9) or umbilical vein (15,30,42) can undergo conversion from cuboidal to spindle-like morphology, strongly reminiscent of KS tumor cells, upon infection by KSHV in vitro.Here we show that such morphological changes are due to the cell-autonomous action of latent viral gene products and occur in both lymphatic and vascular endothelium. By expressing the known KSHV latency genes individually in primary endothelial cells, we show that this morphological change can be effected by a single viral gene encoding the vFLIP protein.…”
mentioning
confidence: 99%